Child burials in domestic contexts at an Iron Age hillfort: The Oppidum of Monte Bernorio (Villarén, Palencia) - Silvia Carnicero-Cáceres (Sociedad de Ciencias Aranzadi, 2021)
The practice of child burials underneath house floors in the Late Prehistory has been considered a characteristic trait of the Iberian religion. However, this custom has also been documented in different archaeological sites both in the Mediterranean and Central Europe as well as Celtic areas of the Iberian Peninsula, so we can explain this funerary practice by an Indo-European origin. We report the archeotanatological and osteoarcheological study of 10 subadults found in the Iron Age site of Monte Bernorio oppidum, the first archeological site in the western and central Cantabrian region with this funerary rite documented. It is the confirmation of both, the survival of an ancient funerary ritual, widely extended in all Europe, and its presence in the north of the Iberian Peninsula. We also review all the archeological sites in the Iberian Peninsula with similar archeological contexts and analyse the rite from the bioarcheology of the care.